2003
DOI: 10.3109/1061186031000150791
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Drug Targeting—Biodistribution of the Magnetic Carrier and the Chemotherapeutic agent Mitoxantrone after Locoregional Cancer Treatment

Abstract: Magnetic Drug Targeting means the specific delivery of chemotherapeutic agents to their desired targets, e.g. tumors, by using magnetic nanoparticles (ferrofluids) bound to these agents and an external magnetic field which is focused on the tumor. This type of target directed drug injection attempts to concentrate a pharmacologic agent by enhancing its efficacy while simultaneously minimizing deleterious side effects. In previous studies, we have been able to demonstrate the efficacy of this type of localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(102 citation statements)
references
References 21 publications
3
94
0
5
Order By: Relevance
“…The accumulation and retention of drug-loaded magnetic nanoparticles in tumors can be enhanced by the attraction of nanoparticles to the tumor location using an externally applied magnetic field. Several studies have already demonstrated the feasibility of magnetic targeting in rodents bearing subcutaneous tumors [2][3][4]. In these studies, magnetic nanoparticles were administered locoregionally into the afferent blood vessels supplying the tumor and a magnetic field source was positioned directly towards the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation and retention of drug-loaded magnetic nanoparticles in tumors can be enhanced by the attraction of nanoparticles to the tumor location using an externally applied magnetic field. Several studies have already demonstrated the feasibility of magnetic targeting in rodents bearing subcutaneous tumors [2][3][4]. In these studies, magnetic nanoparticles were administered locoregionally into the afferent blood vessels supplying the tumor and a magnetic field source was positioned directly towards the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…When an external magnetic field and field gradient are applied, active ingredients bound to or incorporated in these particles are successfully carried to the desired site with relatively high accuracy, minimum surgical intervention, maximum dose, and avoidance of toxic side effects on other organs. [10][11][12] Chitosan is a deacetylated derivative of chitin, a natural polymer found in the shells of crustaceans, and is structurally similar to hyaluronic acid (extracellular matrix). 13,14 The biomedical applications of chitosan have been studied for over 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in ALT and BUN levels reflected the hepatic and renal injury. The magnetic targeting group had markedly lower ALT and BUN levels compared to the MTX group, indicating that magnetic targeting can reduce the side effects of chemotherapeutic drugs and protect the liver, kidneys, and bone marrow from systemic chemotherapy [14] . …”
Section: Resultsmentioning
confidence: 99%